(untitled) (KYAMC Journal, 2018)
Background: Patients with cervical spondylotic radiculopathy is more responding by application of cervical traction with NSAIDs, exercise and ADL than treating with NSAIDs, exercise and ADL. Objectives: Study is to know the effect of home cervical traction on patients with cervical spondylotic radiculopathy. Materials & Methods: A randomized controlled trial was conducted in the department of physical medicine and rehabilitation, BSMMU during the period of 3-9-2012 to 2-9-2013 to find out the effect of home cervical traction on patient with cervical spondylotic radiculopathy. Results: A total of 120 patients with cervical spondylotic radiculopathy attended the department. Sixty patients was treated with NSAID, Isometric neck muscle strengthening exercise, Activity of daily living advice (ADL) and soft cervical collar, other 60 patients was treated with NSAID, Isometric neck muscle strengthening exercise, Activity of daily living advice (ADL) and soft cervical collar with home cervical traction. The patients were treated for 6 weeks. There was marked improvement in both groups after treatment. But there was significant difference regarding improvement in treatment with home cervical traction (p=0.432). Conclusion: So, it can be concluded that the home cervical traction is effective in cervical spondylotic radiculopathy. Male and female ratio was 1.9:.6. In respect of occupation the maximum patient was housewife (27.5%) followed by businessman (25. 8%). Highest number of patients is in the 41-50 years age group. KYAMC Journal Vol. 9, No.-2, July 2018, Page 65-68